DEVELOPMENT PROSPECTS OF FINANCING INVESTMENT PROJECTS IN REAL SECTOR ENTERPRISES - Shernayev Akbar Akmirzayevich (Journals Park Publishing, 2023)
The article deals with the implementation of effective monetary policy and effective banking supervision, the implementation of a prudent policy in attracting foreign capital, ensuring the stability of the national currency, relying mainly on internal sources in the formation of the resource base of banks, and adhering to the principles and rules of credit operations. It was achieved through the use of modern methods of compliance and risk management, and recommendations aimed at further improving the development and operation of the industry were given.
Keywords: monetary policy, banking supervision, global economy, investment activity, financial strategy of enterprises, financial planning, risk management, currency policy, diversification , risk and risks, exchange rate, foreign exchange market, revaluation, balance of payments, currency restrictions.